Xa39, a novel dominant gene conferring broad‐spectrum resistance to Xanthomonas oryzae pv. oryzae in rice. (8th September 2014) - Zhang, F.; Zhuo, D.‐L.; Zhang, F.; Huang, L.‐Y.; Wang, W.‐S.; Xu, J.‐L.; Vera Cruz, C.; Li, Z.‐K.; Zhou, Y.‐L.
<x xml:space="preserve">Abstract</x> Bacterial blight (BB), caused by Xanthomonas oryzae pv. oryzae (Xoo), is one of the most devastating rice diseases worldwide. In this study, a rice introgression line (IL), FF329, which was identified from a BC1F4 population derived from the cross between donor PSBRC66 (P66) and recipient Huang‐Hua‐Zhan (HHZ), exhibited a typical hypersensitive response (HR) when inoculated with all 21 representative Xoo strains, consisting of 14 Philippines races and seven Chinese pathotypes. By contrast, the parents were highly susceptible to 10 of the tested strains and resistant or moderately susceptible to 11 strains, but without HR symptoms. Genetic analysis of the F2 population derived from the HHZ/FF329 cross with virulent Philippines race 6 (P6) and Chinese pathotype V (CV) revealed that BB resistance in FF329 was controlled by a single dominant gene. Because FF329 showed broad‐spectrum BB resistance, different from both parents, the gene identified was novel and was designated Xa39. Two SSR markers, RM21 and RM206, located on rice chromosome 11, were linked to the target gene by bulked segregant analysis. A further six markers linked to Xa39 were identified in the region between RM21 and RM206 for fine gene mapping, and the Xa39 locus was refined to a 97·4 kb interval flanked by markers RM26985 and DM13 using a large F2 population. This gene provides rice breeders with a new option to incorporate BB resistance into newly developed cultivars.